Excitonic structure of absorption edge in quantum dots - Křápek, Vlastimil (2008)
The goal of the thesis is twofold: (i) to develop a theoretical model describing electronic structure and optical properties of quantum dots, and (ii) to apply it to some interesting topics of the quantum dot physics. Effective mass theory was chosen as the appropriate theoretical method for a description of quantum dots, which represents a reasonable trade-off between accuracy and completeness on the one hand, and simplicity, easy interpretation of results and short calculation time on the other hand. In the framework of this approach I have developed a method of approximate variable separation, which enables a numerically simple retrieval of wave functions and energies of bound states in flat quantum dots of arbitrary shape. For a set of important characteristic quantum dot shapes (cone, lens, cylinder), I further implemented a variational method of solution of the Schrödinger equation, which gives more accurate results at the price of slower calculations and lower generality. B.